The SIRE2 Toolkit - J. H. Adams Jr.; Z. D. Robinson; J. H. Nonnast; J. H. Fisher; D. M. Hope; Z. B. Lane; R. A. Reed; J. Z. Fisher; K. M. Warren; B. D. Sierawski (Space Weather)
Abstract The Space Ionizing Radiation Environment and Effects (SIRE2) toolkit has been developed to update and extend the tools used by the space and radiation effects community. It includes new environment models, the capability to examine how the environment changes along satellite and other trajectories and batch processing capabilities for both environments and radiation effects on electronics. An overview of the capabilities in the SIRE2 Toolkit is provided, and examples of applying SIRE2 to satellite orbits and arbitrary trajectories are given.